Low-Income Senior Housing Residents' Emergency Department Use and Care Transition Problems. (December 2018) - Coe, Antoinette B.; Moczygemba, Leticia R.; Ogbonna, Kelechi C.; Parsons, Pamela L.; Slattum, Patricia W.; Mazmanian, Paul E.
Older adults may be at risk of adverse outcomes after emergency department (ED) visits due to ineffective transitions of care. Semi-structured interviews were employed to identify and categorize reasons for ED use and problems that occur during transition from the ED back to home among 14 residents of low-income senior housing. Qualitative thematic and descriptive analyses were used. Ambulance use, timely ED use or a wait-and-see approach, and lack of health-care provider contact before ED visit were emergent themes. Delayed medication receipt, no current medication list, and medication knowledge gaps were identified. Lack of a personal health record, follow-up care instruction, and worsening symptoms education emerged as transition problems from ED to home. After an ED visit, education opportunities exist around seeing primary care providers for nonurgent conditions, follow-up care, medications, and worsening condition symptoms. Timely receipt of discharge medications and medication education may improve medication-related transition problems.